Locally Nilpotent Groups with Weak Conditions of π-Layer Minimality and π-Layer Maximality - Khmelnitskii, N. A.; Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate locally nilpotent groups with weak conditions of π-layer minimality and π-layer maximality.